Positive Scalar Curvature due to the Cokernel of the Classifying Map - Schick, Thomas; Zenobi, Vito Felice (Symmetry, Integrability and Geometry: Methods and Applications, 2020)
This paper contributes to the classification of positive scalar curvature metrics up to bordism and up to concordance. Let be a closed spin manifold of dimension ≥ 5 which admits a metric with positive scalar curvature. We give lower bounds on the rank of the group of psc metrics over up to bordism in terms of the corank of the canonical map ∗() → ∗(Bπ₁()), provided the rational analytic Novikov conjecture is true for π₁().